Odpowiedzi

Najlepsza Odpowiedź!
2010-01-10T12:06:05+01:00
-2x+3y+6=x+2y-6
5x+8y-19=2x-3y-7

-2x+3y-x-2y=-6-6
5x+8y-2x+3y=-7+19

-3x-y=-12
3x+11y=12

10y=0 /:10
y=0

y=0
3x+0=12

y=0
3x=12 /:3

y=0
x=4

Mam nadzieję, że pomogłam, bardzo proszę o najjj... i z góry dziękuję...

Pozdrawiam...
2010-01-10T12:10:33+01:00
-2x+3y+6=x+2y-6
5x+8y-19=2x-3y-7

- 2x - x = -6 - 6 + 2y- 3y
5x - 2x + 8y + 3y = -7 + 19

-3x = -12 -y /: (-3)
3x + 11y = 12

x = 4 + y/3
3 * (4 + y) + 11y = 12

x = 4 + y/3
12 + 3y + 11y = 12

x = 4 + y/3
14y = 12 -12

x = 4 + y/3
14y = 0 /14

x = 4 + y/3
y = 0

x = 4 + y/0
y = 0

x = 4
y =0
2010-01-10T12:12:53+01:00
-2x+3y+6=x+2y-6
5x+8y-19=2x-3y-7

-2x-x+3y-2y=-6-6
5x-2x+8y+3y=-7+19

-3x+y=-12
3x+11y=12

y=-12+3x
3x+11*(-12+3x)=12

y=-12+3x
3x-132+33x=12

y=-12+3x
36x=12+132

y=-12+3x
36x=144 ||:36

y=-12+3x
x=4

y=-12+3*4
x=4

y=-12+12
x=4

y=0
x=4